Ameliorating Effects of Ethanol Extract of Fructus mume on Scopolamine-Induced Memory Impairment in Mice. (1st February 2015) - Kim, Min-Soo; Jeon, Won Kyung; Lee, Kye Wan; Park, Yu Hwa; Han, Jung-Soo
Abstract : We previously reported that Fructus mume ( F. mume ) extract shows protective effects on memory impairments and anti-inflammatory effects induced by chronic cerebral hypoperfusion. Neurodegeneration of basal cholinergic neurons is also observed in the brain with chronic cerebral hypoperfusion. Therefore, the present study was conducted to examine whether F. mume extracts enhance cognitive function via the action of cholinergic neuron using a scopolamine-induced animal model of memory impairments. F. mume (50, 100, or 200 mg/kg) was administered to C57BL/6 mice for 14 days (days 1–14) and memory impairment was induced by scopolamine (1 mg/kg), a muscarinic receptor antagonist for 7 days (days 8–14). Spatial memory was assessed using Morris water maze and hippocampal level of acetylcholinesterase (AChE) and choline acetyltransferase (ChAT) was examined by ELISA and immunoblotting. Mice that received scopolamine alone showed impairments in acquisition and retention in Morris water maze task and increased activity of AChE in the hippocampus. Mice that received F. mume and scopolamine showed no scopolamine-induced memory impairment and increased activity of AChE. In addition, treatments of F. mume increased ChAT expression in the hippocampus. These results indicated that F. mume might enhance cognitive function via action of cholinergic neurons.